2018
DOI: 10.1016/j.bja.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Universal videolaryngoscopy: a structured approach to conversion to videolaryngoscopy for all intubations in an anaesthetic and intensive care department

Abstract: Performing a formal and prolonged trial of mandatory VL in theatre led to changes in perceptions and departmental consensus. As a result of the trial, the department agreed to the use of C-MAC videolaryngoscopy as the default intubation technique throughout theatres and intensive care, with removal of standard Macintosh laryngoscopes from routine use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 40 publications
0
65
0
3
Order By: Relevance
“…EditordWe welcome Caldiroli and Byrne's 1 response to our article, 2 and agree with their further arguments regarding the benefits of universal videolaryngoscopy. One notable point is that this group in Milan has chosen a hyperangulated videolaryngoscope blade, while we have chosen to adopt a Macintosh videolaryngoscope as our 'everyday' tool, backed up by a hyperangulated blade when indicated.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…EditordWe welcome Caldiroli and Byrne's 1 response to our article, 2 and agree with their further arguments regarding the benefits of universal videolaryngoscopy. One notable point is that this group in Milan has chosen a hyperangulated videolaryngoscope blade, while we have chosen to adopt a Macintosh videolaryngoscope as our 'everyday' tool, backed up by a hyperangulated blade when indicated.…”
mentioning
confidence: 55%
“…The use of the green hue is reported to improve visualisation of monitors, as well as distinguish with greater clarity shades of red. 2 Although this improves surgical views, we have noticed an important unintended consequence with interpretation of the colour of syringe labels. For example, interpretation of the colour of Opioid (Pantone 297 blue) 3 and Vasopressor (Pantone 256…”
Section: Declarations Of Interestmentioning
confidence: 94%
“…In 2010, after 6270 documented intubations it was shown to have an incidence of false negative scoring of 0.14%. 6,7 In addition to the advantages cited by Cook and colleagues, 1 we believe that mandating videolaryngoscopy has further advantages: (i) a reduction in the physical workload involved 3 ; (ii) repeatedly using the same equipment provides trainees with the prolonged repetitive practice required to gain expertise 8 ; (iii) training requirements are reduced, in that new staff only need to be trained and assessed in one form of intubation; and (iv) an improvement in teamwork as a result of all staff using the same practice and because of a shared view of the airway. Despite the increased cost of videolaryngoscopy, we agree with Cook and colleagues 1 that this should be seen in the context of the human and financial costs associated with a failure to intubate/oxygenate.…”
Section: Declaration Of Interestmentioning
confidence: 99%
“…a recent study showed that replacing direct laryngoscopy with videolaryngoscopy (vl) as the first-choice departmental technique is perceived by operators as beneficial to patient safety, team dynamics, human factors, and quality of care and quality of training. 54,55 indeed, a recent cochrane review concluded that videolaryngoscopy (VL) reduces intubation difficulty, and the associated trauma. 56 on this regard carassiti et al compared the force and pressure distribution using Macintosh and glidescope laryngoscopes in normal airway by using film pressure transducers.…”
Section: Copyright © 2019 Edizioni Minerva Medicamentioning
confidence: 99%